Activity-Based management Final report - American Productivity & Quality Center; American Productivity & Quality Center (APQC American Productivity & Quality Center, 1996)
This four-volume set provides a comprehensive look at activity-based management (ABM). Taken from four years of research at leading organizations, the APQC Best-practice Reports included in this collection detail how ABM can be used to improve operations and address specifics ranging from technology to strategy to shared services. Learn about system development, reporting, revenue-enhancing management activities, and more. Forty best-practice organizations are examined. The collection includes: Activity-Based Management, Activity-Based Management II: Best Practices for Dramatic Improvement, Activity-Based Management III: Best Practices for Strategic Improvement, and Activity-Based Management 2000: Best Practices in shared Services and Information Technology. Discover how leading organizations use activity-based management (ABM) to improve their processes. Learn how best-practice organizations utilize the full value and potential of ABM information to implement ABM technology and measure results in Activity-Based Management.